2014
DOI: 10.3109/08039488.2014.972454
|View full text |Cite
|
Sign up to set email alerts
|

Is suppressed thyroid-stimulating hormone (TSH) associated with subclinical depression in the Danish General Suburban Population Study?

Abstract: This population-based study supports that persons with suppressed TSH (subclinical hyperthyroidism) seem to have a risk, although small, of subclinical depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 20 publications
1
12
1
6
Order By: Relevance
“…Persons with hypothyroidism are at a risk of depression and have also been suggested by several authors. [ 33 34 35 36 ] Hence, our study also is in concordance with the previous data regarding the comorbidity of depression and hypothyroidism as 60%.…”
Section: Discussionsupporting
confidence: 92%
“…Persons with hypothyroidism are at a risk of depression and have also been suggested by several authors. [ 33 34 35 36 ] Hence, our study also is in concordance with the previous data regarding the comorbidity of depression and hypothyroidism as 60%.…”
Section: Discussionsupporting
confidence: 92%
“…Mild (subclinical) hypothyroidism was defined as TSH > 3.7 mU/L and fT 4 and tT 3 within the reference interval, no history of thyroid disease, and no intake of T 4 /T 3 or antithyroid medication. Controls were defined as having 0.4 < TSH ≤ 3.7 mU/L and fT 4 and tT 3 within the reference interval, no history of thyroid disease, and no intake of T 4 /T 3 or antithyroid medication [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Evidence for the association between TSH levels and depression is conflicting, and even though it is complicated to compare our study to other cross‐sectional analysis, it is possible that our findings expand the results of three previous studies on subjects with subclinical thyroid dysfunction and euthyroidism. A study by Kvetny et al 5 , which analysed a sample of 14,787 men and women from the Danish General Suburban Population Study (GESUS), found that low TSH levels were associated with higher prevalence of depression, when assessed using the Major Depression Inventory. Panicker et al 6 , with a sample of 33,234 from The Nord‐Trøndelag Health Study (HUNT study), found that higher TSH levels were associated with lower risk of depression.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the possible relationship between subclinical thyroid dysfunction and depression, studies have focused on thyroid‐stimulating hormone (TSH) levels. In cross‐sectional analysis, studies reported an association between low TSH levels and depression in men 4,5 and women 5 . Furthermore, high TSH levels were associated with lower risk of depression in men 6 and women 6,7 .…”
Section: Introductionmentioning
confidence: 99%